EMPLOYEE RETENTION IN THE INDIAN RETAIL SECTOR: ROLE OF ORGANIZATIONAL CULTURE, COMPENSATION, AND CAREER GROWTH (Journal of Informatics Education and Research, 2025)
Employee retention is a significant issue in the Indian retail sector with 30-35% annual attrition. The contribution of organizational culture, compensation, and career growth toward enhancing employee retention within the fast-paced retail industry is analyzed through this research. Through a mixed-methods approach, 250 frontline, middle-level, and senior-level employees in organized retail firms took part. The study identifies that positive organisational culture along the lines of being inclusive, respectful, and work-life facilitating has a tremendous influence on retaining employees by developing employee commitment as well as decreasing turnover intentions from the organisation. Reward and distributive compensation policies, particularly non-compensatory ones such as health cover as well as adaptable working hours, play a really significant role in retaining employees. Opportunities for career growth, e.g., promotions, training, and mentorship programs, also make considerable contributions toward retaining the loyalty and satisfaction of employees.